Macroporous high-temperature insulators physical properties by in situ CA6 formation: Does the calcium source matter?. Issue 10 (August 2020) - Borges, O.H.; Santos Junior, T.; Oliveira, R.R.B.; Salvini, V.R.; Pandolfelli, V.C.
Abstract: Aiming the in situ formation of CA6 (CaO·6Al2 O3 ) at alumina-based macroporous insulators, distinct Ca 2+ sources and contents were used and their effect on some of the refractories properties were investigated. Adding CaCO3, Ca(OH)2 or CaO resulted in the decrease of the onset strengthening temperature (TS ) and also of the linear shrinkage. However, a higher amount of Ca(OH)2 and CaO could not be used because of their effect on reducing the insulator total porosity. The composition prepared with 12.9 wt% of CaCO3 was the most promising one, leading to an expansion of 0.81 % after firing at 1600 °C for 5 h, TS of 680 °C and low thermal conductivity. These results point out the potential reduction of sintering temperatures and to the possibility of in situ firing the ceramic insulator. These features enable the development of a macroporous refractory composition with a higher thermal insulating effectiveness, which can help industries to decrease their energy demand.